Mirror Illusion Modulates M1 Activities and Functional Connectivity Patterns of Perceptual–Attention Circuits During Bimanual Movements: A Magnetoencephalography Study - Cheng, Chia-Hsiung; Lin, Szu-Hung; Wu, Ching-Yi; Liao, Yi-Han; Chang, Ku-Chou; Hsieh, Yu-Wei (Frontiers in Neuroscience, 2020)
We differentiated the influence of mirror-induced visual conflicts on the perceptual-attention-motor control process by examining the variation of primary motor cortex (M1) activities and the functional connectivity among five brain regions associated with perceptual, motor, and attentional processes. Magnetoencephalography was recorded under three conditions: both hands kept stationary with the forearms supinated (resting condition), in-phase bimanual movements with congruent visual feedback (symmetry condition), and out-of-phase bimanual movements with incongruent visual feedback (asymmetry condition). We found that compared with the resting state, the decrease in beta oscillation was greater in the symmetry than in the asymmetry condition, suggesting a greater activation of M1 when implementing hand movement without visual conflict. The results of functional connectivity patterns showed that the alpha band functional connectivity between V1 and superior temporal gyrus and the gamma band functional connectivity between the precuneus and posterior cingulate cortex triggered greater or slightly greater coherence strength in the asymmetry condition than in the symmetry condition. However, the beta band functional connectivity showed no difference between the two conditions in all pairs of the brain regions. These findings confirm and extend the previous findings to provide evidence that mirror visual feedback engages the functional networks associated with the perceptual-attentional process and triggers M1 activation, although the M1 activation is functionally independent of with other brain regions unrelated to motor function. In summary, this study demonstrated a concrete functional connectivity pattern for motor control in the face of visual conflicts, providing a foundation for future research to examine the dynamic functional networks of mirror illusion in motor control.